Lymph Leakage Promotes Immunosuppression by Enhancing Anti-Inflammatory Macrophage Polarization - Herrada, Andrés A.; Olate-Briones, Alexandra; Lazo-Amador, Rodrigo; Liu, Chaohong; Hernández-Rojas, Bairon; Riadi, Gonzalo; Escobedo, Noelia (Frontiers in Immunology, 2022)
Lymphatic vasculature is a network of capillaries and vessels capable of draining extracellular fluid back to blood circulation and to facilitate immune cell migration. Although the role of the lymphatic vasculature as coordinator of fluid homeostasis has been extensively studied, the consequences of abnormal lymphatic vasculature function and impaired lymph drainage have been mostly unexplored. Here, by using the Prox1+/– mice with defective lymphatic vasculature and lymphatic leakage, we provide evidence showing that lymph leakage induces an immunosuppressive environment by promoting anti-inflammatory M2 macrophage polarization in different inflammatory conditions. In fact, by using a mouse model of tail lymphedema where lymphatic vessels are thermal ablated leading to lymph accumulation, an increasing number of anti-inflammatory M2 macrophages are found in the lymphedematous tissue. Moreover, RNA-seq analysis from different human tumors shows that reduced lymphatic signature, a hallmark of lymphatic dysfunction, is associated with increased M2 and reduced M1 macrophage signatures, impacting the survival of the patients. In summary, we show that lymphatic vascular leakage promotes an immunosuppressive environment by enhancing anti-inflammatory macrophage differentiation, with relevance in clinical conditions such as inflammatory bowel diseases or cancer.